Coupled lattice-charge-magnetic fluctuations for nonlocal flux mediated pairing in cuprate superconductors - Xi Chen; Yuchuang Cao; Jianghui Pan; Jiahao Dong; Changkai Luo; Xin Li (npj Computational Materials)
Abstract Dynamic charge transfers, or charge flux oscillations, generated by anharmonic phonon coupling, have attracted increasing interest in cuprate superconductors. In this article, a new computational method is developed to analyze such charge fluxes along all atomic bonds for a given material, which unveils a surprising fact that cuprate materials with high superconducting transition temperature show a strong tendency to support global charge flux flows beyond local charge oscillations. Such fluxes further show a strong correlation with both the maximum superconducting transition temperature of different cuprate families and the strong magnetic fluctuations as well. Motivated by these findings, we construct a charge flux model derived from quantum field theory to evaluate the effective interactions mediated by these flux flows. Finally, we discuss the implications of this flux-driven pairing mechanism for the design of new high-Tc superconductors, offering a potential strategy for discovering higher Tc superconductive materials.